Citizenship in Democratic Governance among Phetchabun Province Residents - Thasunthorn, Apinan (King Prajadhipok’s Institute Journal, 2024)
This research aimed to assess the knowledge and understanding of democratic governance among Phetchabun province residents and identify effective strategies for promoting such knowledge and understanding. The research utilized a mixed-methods approach, combining quantitative and qualitative research methods. The quantitative phase involved a sample of 400 individuals, with data collection conducted through a questionnaire. Statistical software was used for data analysis, including calculating percentages, means, and standard deviations. The qualitative phase included a sample group of six experts, academics, and government officials. In-depth interviews were conducted to collect data, and the analysis encompassed a comprehensive examination of both data and data collection methods. The research findings revealed the following results: The level of knowledge and understanding regarding citizenship in the democratic system was moderately satisfactory, with an average score of 3.49 and a standard deviation of 0.37. Several challenges hindered the development of accurate knowledge and understanding regarding democratic governance, including: (1) Insufficient knowledge and understanding of democratic governance, (2) Political polarization and divergent opinions, and (3) A political culture influenced by personal and patronage systems. The strategies to promote knowledge and understanding of democratic governance included educational initiatives which raised awareness about the significance of democratic governance through educational programs, promoting political participation that encouraged citizen involvement in political activities, and strengthening the role of civil society in monitoring the exercise of state power. The recommendations were that government agencies in Phetchabun province should establish a network and develop a curriculum focused on democratic governance, and continuous public relations activities should be undertaken to disseminate vital information and knowledge about Thai citizenship within a democratic system-utilize diverse media channels and involve participation in various political events.